2020
DOI: 10.1002/jcsm.12534
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of multidomain interventions to improve physical frailty, depression and cognition: data from cluster‐randomized controlled trials

Abstract: Background Frailty is the pre‐eminent exigency of aging. Although frailty‐related impairments are preventable, and multidomain interventions appear more effective than unimodal ones, the optimal components remain uncertain. Methods We devised multidomain interventions against physical and cognitive decline among prefrail/frail community‐dwelling ≥65‐year‐olds and evaluated these in complementary cluster‐randomized trials of efficacy and participant empowerment. The Efficacy Study compared ~3‐monthly telephone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
115
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 82 publications
(118 citation statements)
references
References 43 publications
(171 reference statements)
3
115
0
Order By: Relevance
“…We selected articles investigating nutrition interventions, macronutrient intake below recommended, and micronutrient deficiency. We found 26 articles: 10 clinical trials, 3,25–33 five cross‐sectional studies, 34–38 three experimental animal studies 39–41 (one of which also included a human cross‐sectional analysis 38 ), three narrative reviews, 6,42,43 two retrospective studies, 44,45 two systematic reviews or meta‐analyses, 46,47 and one questionnaire survey 48 . Within the 320 original and review articles published in 2018, 2019, and 2020 in JCSM , the 26 articles on nutrition that we found comprise approximately 8%.…”
Section: Taking a Stand: Journal Of Cachexia Sarcopenia And Muscle Nmentioning
confidence: 92%
“…We selected articles investigating nutrition interventions, macronutrient intake below recommended, and micronutrient deficiency. We found 26 articles: 10 clinical trials, 3,25–33 five cross‐sectional studies, 34–38 three experimental animal studies 39–41 (one of which also included a human cross‐sectional analysis 38 ), three narrative reviews, 6,42,43 two retrospective studies, 44,45 two systematic reviews or meta‐analyses, 46,47 and one questionnaire survey 48 . Within the 320 original and review articles published in 2018, 2019, and 2020 in JCSM , the 26 articles on nutrition that we found comprise approximately 8%.…”
Section: Taking a Stand: Journal Of Cachexia Sarcopenia And Muscle Nmentioning
confidence: 92%
“…21 Under those circumstances, appropriate case-finding processes accompanied by protective intervention against cognitive decline has become the main task in dementia prevention. 7 The results of this study suggested that the computerized NCGG-FAT Chinese version might be a potential solution to promote cognitive health in communities with minimal resources. In traditional neurocognitive batteries, there is heavy involvement of healthcare professionals, which require extensive time and effort; however, the computerized NCGG-FAT Chinese version conducted by non-professional personnel has the great potential to enhance community-based health promotion interventions.…”
Section: Discussionmentioning
confidence: 81%
“…Once the circle was correctly selected, the circle would be filled in yellow; an alarm sound would ring if incorrect selections were made. In TMT-B test, circles involved both numbers (1)(2)(3)(4)(5)(6)(7)(8) and English alphabets (A-G). Linking numbers and alphabets alternately (1-A-2-B-3-C, etc.)…”
Section: Components Of the Ncgg-fat Chinese Versionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that multidomain intervention programs substantially improved physical function, cognitive performance, depressive mood and nutritional status among community-dwelling older adults. However, the effects decay as the intervention gradually shifted from group-based to home-based programs, and study also indicated that using simple pedometer improved the adherence to the home activities ( Chen et al, 2020 ). Hence, the results clearly highlighted the potentials of using wearable devices to improve the efficacy of healthy aging programs.…”
mentioning
confidence: 99%